Isolated abducens nerve paresis associated with incomplete Horner's syndrome caused by petrous apex fracture - Case report and anatomical study - Ozveren, MF; Uchida, K; Erol, FS; Tiftikci, MT; Cobanoglu, B; Kawase, T (Japan Neurosurgical Soc, 2001)
A 17-year-old male presented with a wound on the right temporal region, oozing hemorrhagic necrotic brain tissue and cerebrospinal fluid, following a fall. Computed tomography showed temporoparietal and petrous apex fractures on the right. Neurological examination revealed abducens nerve paresis, ptosis, and myosis on the right side. The patient was treated surgically for the removal of the free bony fragments at the fracture site and to close the dural tear. The abducens nerve paresis, ptosis, and myosis persisted at the 3rd monthly postoperative follow-up examination. The anatomy of the abducens nerve at the petroclival region was studied in four cadaveric heads. Two silicone-injected heads were used for microsurgical dissections and two for histological sections. The abducens nerve has three different angulations in the petroclival region, located at the dural entrance porus, the petrous apex, and the lateral wall of the cavernous segment of the internal carotid artery. The abducens nerve had fine anastomoses with the trigeminal nerve and the periarterial sympathetic plexus. There were fibrous connections extending inside the venous space of the petroclival area. The abducens nerve seems to be vulnerable to damage in the petroclival region, either directly by trauma to its dural porus and petrous apex or indirectly by stretching of the nerve through the nervous and/or fibrous connections. Concurrent functional loss of the abducens nerve and the periarterial sympathetic plexus clinically manifested as incomplete Horner's syndrome in our patient.
Keywords: abducens nerve; incomplete Horner's syndrome; petrous apex fracture; sympathetic plexus